RESILIENSI ORANG DENGAN HIV/AIDS DAMPINGAN YAYASAN SAHABAT SEHAT MITRA SEBAYA DI KABUPATEN SUKOHARJO - Ginata, Selva Gigih; Aritonang, Nelson (Indonesian Journal of Social Work, 2023)
ABSTRACT This research is motivated by the stigma and discrimination received by people living with HIV/AIDS in Sukoharjo. Purpose of writing this scientifict paper is to describe the level of resilience of PLWHA assisted by YASEMA. Method used in this scientifict paper is quantitative methods with descriptive methods, a population of 40 people living with HIV and a sample of 40 respondents. The data collection technique used is a questionnaire in the form of Resilience Questions-Test which is equipped with observation and study documentation. The data analysis technique was carried out using descriptive statistical data. Result of this scientifict paper uses seven aspects according to Reivich & Shatte with scores: emotion regulation (842), impulse control (833), optimism (943), analysis of the causes of problems (789), empathy (831), self-efficacy (769), and reaching out (936). The conclusion from the results of this study is that the resilience level of PLWHA assisted by YASEMA is at a moderate level and the range is close to low resilience. Based on the results of this study, the researcher offers a program to increase the resilience of PLWHA assisted by YASEMA Sukoharjo through the program "Increasing the Resilience of PLWHA Assisted by the Sahabat Sehat Mitra Sebaya Foundation in Sukoharjo through Self Help Groups”.